Evaluation of Locally Available Botanicals for the Management of Maize Weevil (Sitophilus zeamais Motsch.) in Room Storage Condition - Bishnu Prasad Neupane; Prem Nidhi Sharma; Sunil Aryal; Jiban Shrestha (Psyche: A Journal of Entomology, 2022)
From April to July 2019, an experiment was conducted in Khumaltar, Lalitpur (27°39.312′N, 85° 19.586′E, and 1322 m above sea level) to assess the effectiveness of plant materials on maize weevil (Sitophilus zeamais Motsch.) control under laboratory conditions (maintained room temperature of 28.5 ± 2°C, and relative humidity of 72 ± 5%) treatments were Acorus calamus (rhizome powder) @ 5 g·kg−1, Melia azadirach (rhizome powder) seed) @ 5 g·kg−1, Curcuma domestica (rhizome powder) @ 5 g·kg−1, mustard oil @ 2 mL·kg−1, Gingiber officinalis (rhizome powder) @ 5 g·kg−1, rice husk ash @ 5 g·kg−1, and an untreated control. These treatments were evaluated in a completely randomized design (CRD) with three replications. At four months, the grains treated with Acorus calamus had the least weight loss (6.66%), and grain damage (1.23%). Grain damage (18%), and weight loss (62.33%) were the highest in the control treatment. Similarly, grains treated with Acorus calamus had the fewest number of exit holes (3.10 per 100 g of maize seed), while the control treatment had the largest number of exit holes (45.10 per 100 g of maize seed). There was a significantly higher number of weevils in the control treatment (55.80 per 250 g maize grains), but only a few numbers of weevils in the Acorus calamus-treated grains (2.50 per 250 g maize grains). In contrast with other plant materials treated grains, the maize weevil showed a reduced preference for Acorus calamus- treated grains with low weight loss, and grain damage. These findings can be used to promote locally accessible botanicals for maize weevil control in Nepal.